The Influence of Organizational Culture and Work Environment on Employee Performance: The Mediating Role of Work Engagement at Pt Pamapersada Nusantara Tanjung Enim - Fandi Andriansyah; Muhammad Ichsan Hadjri; Shelfi Malinda; Zunaidah; Yos Karimudin (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of organizational culture and work environment on employee performance through work engagement at PT Pamapersada Nusantara Tanjung Enim. A cross-sectional census surveyed 120 permanent employees, and data were analyzed using PLS-SEM. Results show that organizational culture has no significant direct effect on performance but negatively affects engagement, whereas the work environment positively affects both engagement and performance. Engagement positively affects performance and mediates both relationships: negative indirect mediation for organizational culture and complementary partial mediation for the work environment. These findings highlight the importance of supportive working conditions and employee engagement in improving performance. Keywords: Organizational Culture; Work Environment; Work Engagement; Employee Performance; Mining Industry